Age and Its Association with Low Insulin and High Amyloid-β Peptides in Blood - Li, Huajie (J Alzheimers Dis, 2015)
Age is the major risk factor for developing Alzheimer’s disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ(40). Apolipoprotein E4 allele (ApoE4) and cognitive impairment were characterized. Subjects were divided into three age groups: 60–70, 70–80, and ≥80 years old. We found that the older the subjects, the lower the concentration of insulin (p = 0.001) and the higher the concentration of Aβ(1–40) (p = 0.004) in plasma. However, age was not associated with the concentration of another pancreatic peptide, amylin, and only marginally with Aβ(1–42). These relationships remained in the absence of diabetes, cardiovascular disease, and stroke, and regardless of the presence of ApoE4 and cognitive impairment. Both age and ApoE4 were inversely associated with, while insulin was positively associated with, the activities of Aβ degradation in serum. Our study suggested that low concentration of insulin and high concentration of Aβ(40) are aging factors related to the risk of AD.